Análise genômica de Limosilactobacillus fermentum ATCC 23271, uma linhagem com potencial probiótico e atividade anti-Candida - SANTOS, Camilla Itapary dos (2021)
Several microorganisms have been studied as potential probiotics in recent years. Some of these studies show health benefits, including in human clinical trials. These benefits may be related to its ability to regulate the intestinal microbiota through competition for adhesion sites, as well as the production of antimicrobial compounds and/or by presenting immunomodulatory effects. This study aimed to perform a genomic analysis of Limosilactobacillus fermentum ATCC 23271 in relation to its use as a probiotic microorganism. For this, the genomic sequencing of the strain was performed, followed by phylogenetic analysis in comparison with the genomes of other strains of L. fermentum, as well as analysis in different databases to detect potential genes that code for proteins related to tolerance to bile salts, digestive enzymes and acid pH, genes associated with the adhesion properties, bacteriocin production and genes related to the strain safety for human use. In vitro tests were also performed to confirm antimicrobial activity and interference with pathogen adhesion. Genome analysis revealed that the ATCC 23271 strain has 2,193,335 bp, with 2,123 protein coding sequences and a guanine-cytosine content of 50.9%. Phylogenetic analysis revealed that the ATCC 23271 strain shares 941 gene clusters with six other probiotic strains of L. fermentum, but only 13 clusters are unique to ATCC 23271. Genes known to confer probiotic properties have been identified in its genome, including genes related to adhesion, tolerance to acid pH and bile salts, tolerance to oxidative stress, metabolism and transport of sugars and other compounds. The BAGEL 4 program showed the presence of a hypothetical protein with low similarity with enterolysin A. The strain proved to be safe for human use, because its genome did not reveal genes of acquired resistance to antibiotics or genes related to virulence, not being characterized as a human pathogen. Furthermore, gene loci associated with CRISPR/CRISPR sequences and two incomplete regions of prophage were detected in the genome, which would limit the spread of possible acquired resistance genes. Tolerance to bile salts (0.5 and 1.0%) and acid pH (pH 2. and 4.0) has been demonstrated in vitro. The ability to inhibit the adhesion of some Candida strains to HeLa cells, especially the genital clinical isolates, was observed in competition and displacement assays. In the antagonism assay, it was confirmed that the strain has antifungal capacity, since it inhibited different strains of Candida spp., except two of C. krusei, without relevant inhibition of the tested bacteria. Furthermore, all antibiotics to which L. fermentum ATCC 23271 showed resistance or was moderately susceptible were suggestive of intrinsic, but not of acquired resistance. Our data revealed that L. fermentum ATCC 23271 has genomic features that demonstrate it is a promising strain for use as a probiotic due to its functional benefits, especially against Candida infections.